6-3z=-5z-8

Simple and best practice solution for 6-3z=-5z-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3z=-5z-8 equation:


Simplifying
6 + -3z = -5z + -8

Reorder the terms:
6 + -3z = -8 + -5z

Solving
6 + -3z = -8 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
6 + -3z + 5z = -8 + -5z + 5z

Combine like terms: -3z + 5z = 2z
6 + 2z = -8 + -5z + 5z

Combine like terms: -5z + 5z = 0
6 + 2z = -8 + 0
6 + 2z = -8

Add '-6' to each side of the equation.
6 + -6 + 2z = -8 + -6

Combine like terms: 6 + -6 = 0
0 + 2z = -8 + -6
2z = -8 + -6

Combine like terms: -8 + -6 = -14
2z = -14

Divide each side by '2'.
z = -7

Simplifying
z = -7

See similar equations:

| g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 | | 6x+13=-5x-18 | | -9+9p=10p | | -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 | | 5-w=-16 | | 7x+10=-5x-16 | | 6x+6+2y=66 | | -5[x+6]=-5x+9 | | 12-21=-9 | | 3-6+2-1+8= | | 0.5x+3=2.5x-6 | | X-5+3x=6x-16 | | 3-3*6+2=l | | 2000=16t^2 | | .09k+13(k+300)=61 | | 2x-y=150 | | 2b+6.7=13.2-8b | | -37y=-36x+1 | | 9y=-4x+1 | | 6-k=7k-5k | | 25x-8=72 | | (180-x)=4x | | 4a=(180-x) | | e^2z+1=0 | | 6x*6xy= | | x^3-25x^2=15 |

Equations solver categories